NEW ASPECTS OF TEACHING INFORMATICS IN PEDAGOGICAL UNIVERSITIES - Nuraliev Umidjon Abdukarimovich (Galaxy International Interdisciplinary Research Journal, 2022)
The paper is devoted to a promising development of a methodological system for the formation of a teacher’s professional competence and concludes that pedagogical design today is a powerful toolkit in the hands of a teacher, allowing you to create and implement a project for solving a pedagogical problem.